A study of the perceptions of undergraduates towards marriage and the family. - Kwok, Imm Mui. (2008)
This study aims to look into the perceptions of university graduates towards marriage and the family in view of later marriages and delayed child-bearing in Singapore. Assuming that the undergraduate is a close proxy of the graduate, the undergraduates in Nanyang Technological University (NTU) were surveyed. It is hoped that the findings and recommendations suggested in this research will be useful in promoting the concept of marriage and family among graduates.